2021
DOI: 10.1371/journal.pone.0249276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic activities of aconitine in different mice pain models

Abstract: Aconitine (AC) is the primary bioactive and secondary metabolite alkaloidin of Aconitum species which is accounted for more than 60% of the total diester-diterpenoid alkaloids in Aconite. To evaluate the analgesic effects of AC, 4 different pain models including hot plate assay, acetic acid writhing assay, formalin and CFA induced pain models were adopted in this study. In hot plate experiment, AC treatment at concentration of 0.3 mg/kg and 0.9 mg/kg improved the pain thresholds of mice similar to the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Accumulating evidence suggests that phytochemicals can affect the central nervous system by crossing the BBB. Thus, these phytochemicals may have played a role in the analgesic effect of JI017 as decursin has been reported to attenuate paclitaxel-induced pain and to act as an TRPV1 antagonist [65], while aconitine has also been shown to have an analgesic effect on various animal models of pain [66]. The analgesic effect of 6-gingerol was also reported in several studies [67][68][69].…”
Section: Discussionmentioning
confidence: 83%
“…Accumulating evidence suggests that phytochemicals can affect the central nervous system by crossing the BBB. Thus, these phytochemicals may have played a role in the analgesic effect of JI017 as decursin has been reported to attenuate paclitaxel-induced pain and to act as an TRPV1 antagonist [65], while aconitine has also been shown to have an analgesic effect on various animal models of pain [66]. The analgesic effect of 6-gingerol was also reported in several studies [67][68][69].…”
Section: Discussionmentioning
confidence: 83%
“…The animal reacts to the pain triggered by the chemical stimuli by licking its paw. Paw licking time was recorded for the first five minutes after the formalin injection as an indicator of acute pain and between the 15th and 30th min of injection, indicating chronic pain [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 30 min of administration of the extracts, the animals were intraperitoneally injected with 0.6% of acetic acid. Then, the number of writhes produced in the mice within 15 min was counted for 20 min [ 56 ]. The analgesic effect was measured by calculating the reduction in the mean number of abdominal writhing for each group as compared to the control.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence that AC has significant therapeutic effect on the nervous system, can significantly prolong the incubation period of writhing, and reduce the number of writhing in mice, effectively decreasing the pain sensation elicited by acetic acid [21,22]. In addition, some scholars used four different pain models including hot plate assay, acetic acid writhing assay, formalin, and CFA to evaluate the analgesic effect of AC, and the results also verified the obvious analgesic effects of AC [23]. Kang et al further found that iontophoresis of AC can reduce the local 5‐HT content in inflammatory tissue of the adjuvant arthritis rats and increase the content of 5‐HT, norepinephrine (NE), and hypothalamus β‐EP and produce analgesic effect [24].…”
Section: Biological Activitymentioning
confidence: 99%